Just me and my puppy - Mayer, Mercer, 1943- (New York : Golden Books Pub., 1985)
Even though Puppy misbehaves, he makes a wonderful pet.
"Little Critter."
1.5
K-3
K-3
Keywords: Dogs -- Fiction; Animals -- Infancy -- Fiction; Pets -- Fiction; Little Critter (Fictitious character) -- Fiction; Dogs -- Fiction; Animal babies; Pets -- Fiction; Little Critter (Fictional character) -- Fiction